Inside/outside the brain binary cavitation localization based on the lowpass filter effect of the skull on the harmonic content: a proof of concept study. (2nd July 2018) - Maimbourg, Guillaume; Houdouin, Alexandre; Santin, Mathieu; Lehericy, Stéphane; Tanter, Mickael; Aubry, Jean-François
Abstract: Cavitation activity induced by ultrasound may occur during high intensity focused ultrasound (HIFU) treatment, due to bubble nucleation under high peak negative pressure, and during blood–brain–barrier (BBB) disruption, due to injected ultrasound contrast agents (UCAs). Such microbubble activity has to be monitored to assess the safety and efficiency of ultrasonic brain treatments. In this study, we aim at assessing whether cavitation occurs within cerebral tissue by binary discriminating cavitation activity originating from the inside or the outside of the skull. The results were obtained from both in vitro experiments mimicking BBB opening, by using UCA flow, and in vitro thermal necrosis in calf brain samples. The sonication was applied using a 1 MHz focused transducer and the acoustic response of the microbubbles was recorded with a wideband passive cavitation detector. The spectral content of the recorded signal was used to localize microbubble activity. Since the skull acts as a low pass filter, the ratio of high harmonics to low harmonics is lower for cavitation events located inside the skull compared to events outside the skull. Experiments showed that the ratio of the 5/2 ultraharmonic to the 1/2 subharmonic for binary localization cavitation activity achieves 100% sensitivity and specificity for both monkey and human skulls. The harmonic ratio of the fourth to the second harmonic provided 100% sensitivity and 96% and 46% specificity on a non-human primate for thermal necrosis and BBB opening, respectively. Nonetheless, the harmonic ratio remains promising for human applications, as the experiments showed 100% sensitivity and 100% specificity for both thermal necrosis and BBB opening through the human skull. The study requires further validation on a larger number of skull samples.